Pengaruh Nilai ESG Dengan Kebutuhan Modal Kerja: Analisis Perusahaan Listing Indonesia Periode 2015-2020 - Rahmita, Vani; Rizkianto, Eko; Prabowo, Hendro (Jurnal Manajemen dan Usahawan Indonesia, 2023)
This study aims to analyze the effect of ESG score and its pillars (environmental, social, and governance score), as a proxy of sustainable companies, on working capital requirements (WCR) and cash conversion cycle (CCC) of Indonesian listing companies for the period 2015-2020. The ESG and pillar scores are obtained from the Thomson Reuters Refinitiv Eikon terminal. The research covers 29 non-financial listed companies in Indonesia in the six years with a total of 174 observations through the purposive sampling technique. This study finds that on average non-financial companies in Indonesia use a conservative working capital strategy which makes the company's working capital too large. Based on balance panel data and the robust OLS method, the result shows that ESG and its pillars can be a determinant in working capital. ESG, environmental pillars, and social pillars scores can reduce working capital requirements and shorten cash conversion cycles. Meanwhile, the governance pillar score does not affect working capital. Hence, ESG, environmental pillars, and social pillars can encourage companies to have lower working capital requirements and shorter cash conversion cycles so that companies with high ESG performance tend to use aggressive working capital strategies and turn the business operates more efficiently. Thus, ESG can lead to resource advantage and be a signal of company efficiency.